Optimal Strategies to Increase National Income in Realising Golden Indonesia 2045 - Hali, Azmal; Sadiah, Halimahtus; Dewi, Zahra Devina; Syahputra, Muhammad Zhafran; Desilva, Valendra; Nuraya, Ahmad Setiawan (Indonesian Research Journal on Education, 2025)
The Golden Indonesia 2045 is Indonesia's vision established in 2019, aiming for the country to become developed and prosperous by its centennial of independence. This paper outlines the key factors necessary for Indonesia to rank among the world's top five economies, including enhancing human resource quality, infrastructure development, technological advancement, business transformation, and stakeholder engagement while ensuring national stability. Utilizing a qualitative method, this research analyzes data from various journals and official government reports. The findings indicate that achieving economic independence requires a blend of adaptive fiscal policies, innovative industries, and a skilled workforce, all of which are essential to accelerate Indonesia's economic growth.